Automated Decision-Making Tool That Determines the Most Economic Sampling Plan for Process Validation of Pharmaceutical and Biomédical Products. - Gola, Andres I. (Journal of Validation Technology (JVT))
This paper proposes an automated digital system for the selection of the most cost-friendly process validation sampling plan. The system is based on the US Food and Drug Administration's mandates and other standardized procedures. The algorithm is designed to deliver one output as a function of multiple input parameters without further interaction with the users. The system will reduce any possible subjective elections and will make the output a completely objective and quantitative result.